Activated sludge (Water Environment Federation, 2002)
Annotation This second edition of Activated Sludge, MOP OM-9, represents the most complete information source for the activated sludge process. Well-established design standards based on empirical data have evolved over the years. Despite these advances, poor process performance can still be present problems for many plants. The objective of this manual is to help wastewater professionals acquire a greater knowledge of the process, solve performance problems, and improve operations. This manual serves as the Federation's primary reference for operation of the activated sludge process. It includes the most up to date information on process control to include strategies for controlling the biomass inventory; energy use and energy-saving opportunities; procedures used for solving common operational problems to include new information on troubleshooting for nitrogen and phosphorus removal systems; plus a new section on Aerobic Digestion.
Keywords: Sewage -- Purification -- Activated sludge process -- Handbooks, manuals, etc.; elektronické knihy; electronic books